Dividend Policy and Market Performance of Nigerian Listed Insurance Firms - Adegbie, Festus Folajim; Odunlade, Olajire Aremu; Nwarunma, Ibeabughich (Archives of Business Research, 2023)
The issue of dividend policy has been a source of disagreement and discussion among experts for many years, particularly its impact on market performance. Some argue that dividend policy has an effect on market performance based on signaling theory, while others dispute this claim. Consequently, this study examined the impact of dividend policy on the market performance of listed insurance firms in Nigeria with and without control over return on assets. This study used an ex-post facto research design approach and employed pooled ordinary least squares to analyze data gathered for 10 selected firms from 2008 to 2020. The study’s preliminary analysis revealed that all the employed are positively related. The pooled regression result showed that dividend payout (DVP) had a negative but insignificant impact on market price per share (MSP), while dividend yield (DVY) and dividend per share (DPS) had a positive and significant impact on MSP. Furthermore, the results showed that return on assets had a negative but insignificant impact on the market price per share (MSP), and the adjusted R-squared results revealed that dividend policy explains about 82% of the changes in market performance of the selected insurance firms. The study concluded that dividend policy has a significant impact on market performance, with or without taking return on assets into account. Based on the results, the study recommended that management and shareholders focus on the operational needs of the company and understand the connection between profit maximization and dividend policies.